Management of Cardiovascular Disease in Patients With COVID-19 and Chronic Chagas Disease: Implications to Prevent a Scourge Still Larger - Bestetti, Reinaldo Bulgarelli; Bocchi, Edimar Alcides; Bestetti, Renato; Issa, Victor Sarli; Furlan-Daniel, Rosemary Aparecida; Nakazone, Marcelo Arruda (Frontiers in Medicine, 2022)
Cardiovascular diseases (CVD) are the most important cause of morbidity and mortality in the general population. Because the high prevalence of COVID-19 and chronic Chagas disease (CCD) where the latter is endemic, all such diseases will likely be observed in the same patient. While COVID-19 can provoke generalized endotheliitis, which can lead to a cytokine storm and a hyper-coagulable state culminating into in-site and at a distance thrombosis. Therefore, small-vessel coronary artery disease (CAD), cerebrovascular disease, thromboembolism, and arrhythmias are prominent findings in COVID-19. In CCD, small-vessel CAD, cardioembolic stroke, pulmonary embolism, and arrhythmias are frequently observed as well as a result of a similar but less intense mechanism. Consequently, the association of CCD and COVID-19 will likely increase the incidence of CVD. Thus, doctors on the frontline should be on the alert for this diagnostic possibility so that the proper treatment can be given without any delay.